Estimates of Trade-Related Adjustment Costs in Syria - Lim, Jamus Jerome; Saborowski, Christian (2012)
The scope and complexity of international trading arrangements in the Middle East, as well as their spotty historical record of success, underscores the urgent need for an adequate understanding of the relative costs and benefits of participation in preferential trading arrangements and, more generally, of changes in domestic import regimes. This paper seeks to address this problem by providing estimates of the adjustment costs associated with two broad classes of hypothetical trade policy scenarios for Syria: participation in preferential trading arrangements, and changes in the domestic import regime. The authors find that the revenue consequences of the first scenario may be substantial. Their analysis of the second scenario suggests that the number of tariff bands can be reduced, while ensuring revenue neutrality, via the introduction of a value added tax of sufficient but reasonable size.